2023
DOI: 10.36227/techrxiv.21688352.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the robustness of machine learning models for stress and anxiety recognition from heart activity signals

Abstract: <p>Many recent studies have addressed the detection of negative affective states such as stress and anxiety from physiological signals taken from body-worn sensors. Typically, machine learning classifiers are applied to features derived from sensor signals, and several authors have reported high accuracy results from a range of signals including cardiac, skin conductance and skin temperature. However, the issue of how robust these models are for deployment in the field is rarely addressed. In this paper,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several systematic reviews showed that wearable technology can have a positive impact on sleep, stress, physical activity, depression, emotional regulation, and cardiovascular and metabolic functioning ( 14 , 20 , 24 30 ). Sleep, stress and physical activity are considered transdiagnostic markers of psychiatric problems ( 18 20 ), and can be monitored relatively easy with wearable technology, assuming that the algorithms are accurate and robust ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews showed that wearable technology can have a positive impact on sleep, stress, physical activity, depression, emotional regulation, and cardiovascular and metabolic functioning ( 14 , 20 , 24 30 ). Sleep, stress and physical activity are considered transdiagnostic markers of psychiatric problems ( 18 20 ), and can be monitored relatively easy with wearable technology, assuming that the algorithms are accurate and robust ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have resulted in small to medium effect sizes of wearable technology, including fitness trackers, activity trackers and biofeedback devices on stress, sleep, physical activity, depression, emotional and behavioral self-regulation, cardiovascular functioning, and metabolic syndrome ( 14 , 16 , 20 , 24 31 ). However, the implementation of wearable technology in forensic psychiatry faces challenges, including limited technology readiness, acceptance, usability of the devices, continuous use of the devices, privacy concerns and data management ( 14 , 32 35 ).…”
Section: Introductionmentioning
confidence: 99%